Predominance of Blastocystis sp subtype 4 in rural communities, Nepal - Lee, I.L.; Tan, T.C.; Tan, P.C.; Nanthiney, D.R.; Biraj, M.K.; Surendra, K.M.; Suresh, K.G. (2012)
Blastocystis sp. is a common intestinal parasite. To date, there have been sporadic and scanty studies on Blastocystis sp. carried out in rural communities in Nepal. We surveyed the prevalence of Blastocystis sp. and its possible associated risk factors, and reported the predominant Blastocystis sp. subtype in two rural communities, Bolde Phediche and Bahunipati, in Nepal. Human faecal samples were collected from 241 participants, cultured using in vitro cultivation and examined for Blastocystis sp. The presence of Blastocystis sp. in faecal samples was further confirmed by polymerase chain reaction (PCR) and subsequently genotyped using subtype-specific sequence tagged site (STS) primers. There were 26.1 (63/241) of the participants that were infected by Blastocystis sp. We detected 84.1 (53/63) of Blastocystis sp. subtype 4 infections in these rural communities. The unusually high prevalence of Blastocystis sp. subtype 4 can be attributed to the rearing of family-owned animals in barns built close to their houses. Eighty one percent (51/63) of the Blastocystis sp. infected participants drank not boiled or unfiltered water. The present study revealed that Blastocystis sp. could pose a health concern to the communities and travellers to the hilly area in Nepal. Infection may be transmitted through human-to-human, zoonotic and waterborne transmissions. We provide recommendations to ensure good public health practices.